Silicon carbon material and secondary battery comprising same
By using silicon-carbon materials in lithium-ion batteries, the material consists of porous carbon and silicon-based materials, the problem of short cycle life of silicon-based negative electrode materials is solved, effective expansion relief and high reversible specific capacity are achieved, and the service life of the battery is extended.
Patent Information
- Application Number
- CN202411905431.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
The existing silicon-based negative electrode materials have short cycle life, high expansion rate and poor electrical conductivity, which limits their wide application in lithium-ion batteries.
A silicon carbon material is used, which consists of porous carbon and a silicon-based material located in the porous carbon pores, with a silicon content between 20 wt.% and 70 wt.%. By controlling the relationship between specific surface area BET1 and median particle size Dv501 and median particle size Dv502 of porous carbon (0.8≤BET1×(Dv502/Dv501)≤6.5), in order to alleviate the expansion and contraction effect of the silicon negative electrode and improve the reversible specific capacity.
It effectively alleviates the expansion and contraction effect of the silicon negative electrode, improves the reversible specific capacity, and extends the cycle life of the silicon negative electrode, making silicon carbon materials suitable for the negative electrode active substances of secondary batteries.
Smart Images

Figure BDA0005204264450000121 
Figure BDA0005204264450000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a silicon-carbon material and a secondary battery containing the same. Background Art
[0002] Negative electrode material is one of the most critical materials in lithium-ion battery technology. Currently, the graphite negative electrode on the market has reached a technical bottleneck due to its low gram capacity, while silicon negative electrode material has attracted the attention of researchers due to its high gram capacity and abundant resources. However, the high expansion rate and poor conductivity of silicon negative electrode material have become factors restricting its widespread application. Summary of the invention
[0003] In view of this, the present invention provides a silicon-carbon material to solve the problem of short cycle life of existing silicon-based negative electrode materials.
[0004] In the first aspect, the present invention provides a silicon-carbon material, which comprises porous carbon and a silicon-based material located in the pores of the porous carbon; the silicon content in the silicon-carbon material is 20wt.% to 70wt.%, and the specific surface area BET 1 The median particle size Dv50 of the silicon carbon material 1 , the median particle size Dv50 of the porous carbon 2 The following conditions are met:
[0005] 0.8≤BET 1 ×(Dv50 2 / Dv50 1 )≤6.5;
[0006] Among them, BET 1 The unit is m 2 / g, Dv50 1 and Dv50 2 The unit is μm.
[0007] In an optional embodiment, the silicon content in the silicon-carbon material provided by the present invention is 48 wt.% to 55 wt.%, and satisfies 1.0≤BET 1 ×(Dv50 2 / Dv50 1 )≤3.0.
[0008] In an optional embodiment, the silicon-carbon material provided by the present invention satisfies 0.3m 2 / g≤BET 1 ≤5m 2 / g.
[0009] In an optional embodiment, the silicon-carbon material provided by the present invention satisfies 0.5m 2 / g≤BET1 ≤2m 2 / g.
[0010] In an optional embodiment, the silicon-carbon material provided by the present invention satisfies 1 μm ≤ Dv50 1 ≤20μm.
[0011] In an optional embodiment, the silicon-carbon material provided by the present invention satisfies 2μm≤Dv50 1 ≤10μm.
[0012] In an optional embodiment, in the silicon-carbon material provided by the present invention, the silicon-based material includes one or more of amorphous silicon, crystalline silicon, and a composite of crystalline silicon and amorphous silicon.
[0013] In an optional embodiment, the pore volume of the silicon-carbon material provided by the present invention is less than 0.5 cm 3 / g.
[0014] In an optional embodiment, the pore volume of the silicon-carbon material provided by the present invention is less than 0.1 cm 3 / g.
[0015] In an optional embodiment, the true density of the silicon-carbon material provided by the present invention is 1.5 g / cm 3 ~3g / cm 3 .
[0016] In an optional embodiment, the tap density ρ of the silicon-carbon material provided by the present invention is td Meet: 0.5g / cm 3 ≤ρ td ≤1.2g / cm 3 .
[0017] In an optional embodiment, the compaction density of the silicon-carbon material provided by the present invention at a pressure of 5T is cd Meet: 0.5g / cm 3 ≤ρ cd ≤2g / cm 3 .
[0018] In an optional embodiment, the Raman spectrum of the silicon-carbon material provided by the present invention is D / I G Less than 2.
[0019] In an optional embodiment, in the silicon-carbon material provided by the present invention, the silicon-based material fills 10% to 90% of the pore volume of the porous carbon.
[0020] In an optional embodiment, in the silicon-carbon material provided by the present invention, the silicon-based material fills 20% to 60% of the pore volume of the porous carbon.
[0021] In an optional embodiment, the specific surface area of the porous carbon is BET 2 Meet: 200m 2 / g≤BET 2 ≤4000m 2 / g.
[0022] In an optional embodiment, the specific surface area of the porous carbon is BET 2 Meet: 500m 2 / g≤BET 2 ≤2000m 2 / g.
[0023] In an optional embodiment, the pore volume of the porous carbon is 0.4 cm 3 / g~2.5cm 3 / g.
[0024] In an optional embodiment, the porosity of the porous carbon is 50% to 90%.
[0025] In an optional embodiment, the true density of the porous carbon is 1 g / cm 3 ~3g / cm 3 .
[0026] In an optional embodiment, the silicon-carbon material provided by the present invention further includes a coating layer, and the coating layer includes one or more of a carbon coating layer, an oxide coating layer, a metal salt coating layer, and a polymer coating layer.
[0027] In an optional embodiment, the coating layer has a thickness of 5 nm to 500 nm.
[0028] In an optional embodiment, the mass of the coating layer accounts for 1% to 20% of the total mass of the silicon-carbon material.
[0029] In a second aspect, the present invention further provides a negative electrode plate, which includes a current collector and a membrane arranged on the surface of the current collector, and the membrane includes the silicon-carbon material described in the first aspect.
[0030] In a third aspect, the present invention further provides a secondary battery, comprising a positive electrode plate, the negative electrode plate described in the second aspect of the present invention, and an electrolyte located between the positive electrode plate and the negative electrode plate.
[0031] In a fourth aspect, the present invention further provides an electrical device, comprising the secondary battery described in the third aspect of the present invention.
[0032] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0033] The silicon-carbon material provided by the present invention comprises porous carbon and a silicon-based material located in the pores of the porous carbon. The inventors have found that when the silicon content in the silicon-carbon material is appropriate and the specific surface area BET 1 (m 2 / g) and median particle size Dv50 1 (μm) Median particle size Dv50 of porous carbon 2 (μm) satisfies 0.8≤BET 1 ×(Dv50 2 / Dv50 1 )≤6.5, the silicon-carbon negative electrode material can not only effectively alleviate the expansion and contraction effect of the silicon negative electrode, but also has a higher reversible specific capacity. DETAILED DESCRIPTION
[0034] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0035] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0036] In order to solve the problems existing in the above-mentioned related technologies, according to the first aspect of the present invention, a silicon-carbon material is provided, comprising porous carbon and a silicon-based material located in the pores of the porous carbon; the silicon content in the silicon-carbon material is 20wt.% to 70wt.%; the specific surface area BET 1 The median particle size Dv50 of the silicon carbon material 1 , the median particle size Dv50 of the porous carbon 2 The following conditions are met:
[0037] 0.8≤BET 1 ×(Dv50 2 / Dv50 1 )≤6.5;
[0038] Among them, BET 1 The unit is m 2 / g, Dv50 1 and Dv50 2 The unit is μm.
[0039] The inventors have done a lot of research and found that when the silicon content in the silicon-carbon material is appropriate and the specific surface area BET 1 (m 2 / g) and median particle size Dv50 1 (μm) and the median particle size Dv50 of porous carbon 2 (μm) satisfies 0.8≤BET 1 ×(Dv50 2 / Dv50 1 )≤6.5, the silicon-carbon negative electrode material can effectively alleviate the expansion and contraction effect of the silicon negative electrode and also has a higher reversible specific capacity. Specifically, BET 1 ×(Dv50 2 / Dv50 1 ) can be, but not limited to, 0.8, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5. The silicon content in the silicon-carbon material can be, but not limited to, 20wt.%, 30wt.%, 40wt.%, 48wt.%, 55wt.%, 60wt.%, 70wt.%.
[0040] Furthermore, the inventors have found that when the silicon content in the silicon-carbon material is 48wt.% to 55wt.%, and the silicon-carbon material satisfies 1.0≤BET 1 ×(Dv50 2 / Dv50 1 )≤3.0, the expansion and contraction effect of the silicon negative electrode is smaller and the reversible specific capacity is higher.
[0041] In an optional embodiment, the specific surface area BET of the silicon-carbon material provided by the present invention is 1 Meet 0.3m 2 / g≤BET 1 ≤5m 2 / g; preferably, 0.5m 2 / g≤BET 1 ≤2m 2 / g. The inventors have found that silicon-carbon products with high specific surface areas can lead to excessive consumption of electrolyte and unstable solid electrolyte interface membranes due to volume expansion during the cycle. Therefore, the silicon-carbon material of the present invention has the above-mentioned specific surface area, which can avoid problems such as excessive consumption of electrolyte and unstable solid electrolyte interface membranes, and improve battery stability. Specifically, BET 1 The value can be but is not limited to 0.3m 2 / g, 0.5m 2 / g, 1.0m 2 / g, 1.5m2 / g, 2.0m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g.
[0042] In an optional embodiment, the median particle size Dv50 of the silicon-carbon material provided by the present invention is 1 Meet 1μm≤Dv50 1 ≤20μm, preferably 2μm≤Dv50 1 ≤10μm. The inventors found that when the median particle size Dv50 of the silicon-carbon material 1 When the above conditions are met, it has good processing performance. Specifically, Dv50 1 The value of can be, but is not limited to, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 17 μm, and 20 μm.
[0043] In an optional embodiment, the silicon-based material in the silicon-carbon material provided by the present invention fills 10% to 90% of the pore volume of the porous carbon, preferably 20% to 60%, and after filling, the pore volume of the silicon-carbon material is less than 0.5 cm 3 / g, preferably less than 0.1cm 3 / g, more preferably less than 0.01cm 3 / g. The inventors have found that when the pore volume of the silicon-carbon material meets the above conditions, there are pores inside the porous carbon, which leaves space for the volume expansion of the silicon-based material and improves the cycle performance. Specifically, the value of the pore volume of the silicon-carbon material after filling can be, but is not limited to, 0.45cm 3 / g, 0.4cm 3 / g, 0.3cm 3 / g, 0.2cm 3 / g, 0.1cm 3 / g, 0.05cm 3 / g, 0.01cm 3 / g, 0.005cm 3 / g.
[0044] In an optional embodiment, the true density of the silicon-carbon material provided by the present invention is 1.5 g / cm 3 ~3g / cm 3 , the true density of porous carbon is 1g / cm 3 ~3g / cm 3True density refers to the actual mass of a solid substance per unit volume when the material is absolutely dense, that is, the density after removing the internal pores or pores between particles. Specifically, the true density of silicon-carbon materials can be, but is not limited to, 1.5 cm 3 / g, 2.0cm 3 / g, 2.5cm 3 / g, 3cm 3 / g; the true density of porous carbon can be but is not limited to 1.0 cm 3 / g, 1.5cm 3 / g, 2.0cm 3 / g, 2.5cm 3 / g, 3cm 3 / g.
[0045] In an optional embodiment, the tap density ρ of the silicon-carbon material provided by the present invention is td Meet: 0.5g / cm 3 ≤ρ td ≤1.2g / cm 3 Specifically, the tap density of silicon carbon material is td It can be but not limited to 0.5cm 3 / g, 0.8cm 3 / g, 1.0cm 3 / g, 1.2cm 3 / g.
[0046] In an optional embodiment, the compaction density of the silicon-carbon material provided by the present invention at a pressure of 5T is cd Meet: 0.5g / cm 3 ≤ρ cd ≤2g / cm 3 Specifically, the compaction density of silicon-carbon material under 5T pressure is cd It can be but not limited to 0.5g / cm 3 , 0.8g / cm 3 , 1.0g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 , 1.8g / cm 3 , 2.0g / cm 3 .
[0047] In an optional embodiment, the Raman spectrum of the silicon-carbon material provided by the present invention is D / I G Less than 2. Specifically, in the Raman spectrum of silicon-carbon materials, D / I G It can be, but is not limited to, 1.9, 1.5, 1.0, 0.8, 0.6, 0.4, and 0.2.
[0048] In an optional embodiment, the specific surface area of the porous carbon is BET 2 Meet 200m 2 / g≤BET 2 ≤4000m 2 / g, preferably 500m 2 / g≤BET 2 ≤2000m 2 / g, which ensures that there are more sites for silane to contact with porous carbon, making it easier for silicon-based materials to deposit. Specifically, the specific surface area of porous carbon is BET 2 Can be but not limited to 200m 2 / g、500m 2 / g、800m 2 / g、1000m 2 / g, 2000m 2 / g、3000m 2 / g, 4000m 2 / g.
[0049] In an optional embodiment, the pore volume of the porous carbon is 0.4 cm 3 / g~2.5cm 3 / g. If the pore volume is too small, the deposited silicon content is too low, while if the pore volume is too large, the porous carbon will be fragile and will not have sufficient strength to inhibit the volume expansion of silicon during the charge and discharge process. Specifically, the pore volume of the porous carbon can be, but is not limited to, 0.4 cm 3 / g, 0.8cm 3 / g, 1.2cm 3 / g, 1.6cm 3 / g, 2.0cm 3 / g, 2.2cm 3 / g, 2.5cm 3 / g.
[0050] In an optional embodiment, the porosity of the porous carbon is 50% to 90%, of which the micropores account for 10% to 30% and the mesopores account for 50% to 85%. The inventors have found that porous carbon with a pore size ratio within this range is easier to deposit silicon-based materials. Specifically, the porosity of the porous carbon can be but not limited to 50%, 60%, 70%, 80%, 90%, the micropores account for but not limited to 10%, 20%, 30%, and the mesopores account for but not limited to 50%, 60%, 70%, 80%, 95%.
[0051] In an optional embodiment, the true density of the porous carbon is 1 g / cm 3 ~3g / cm 3Specifically, the true density of porous carbon can be, but is not limited to, 1 g / cm 3 , 1.5g / cm 3 , 2g / cm 3 , 2.5g / cm 3 , 3g / cm 3 .
[0052] It is understood that the specific surface area of the porous carbon described in the present invention is BET 2 , pore volume, porosity, true density, etc., all refer to the structural parameters of the porous carbon raw material itself, rather than the parameters of the porous carbon after the silicon-carbon material is formed.
[0053] In an optional embodiment, the silicon-carbon material further includes a coating layer, and the coating layer includes one or more of a carbon coating layer, an oxide coating layer, a metal salt coating layer, and a polymer coating layer.
[0054] In an optional embodiment, the coating layer has a thickness of 5 nm to 500 nm. Specifically, the coating layer may have a thickness of, but is not limited to, 5 nm, 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, or 500 nm.
[0055] In an optional embodiment, the mass of the coating layer accounts for 1% to 20% of the total mass of the silicon-carbon material. Specifically, the mass of the coating layer may account for, but is not limited to, 1%, 5%, 10%, 15%, or 20% of the total mass of the silicon-carbon material.
[0056] In an optional embodiment, the silicon-carbon material is prepared by depositing a silicon-based material in porous carbon, wherein the silicon-based material is produced by cracking a silicon-containing gas. The method is simple and feasible and can be mass-produced.
[0057] In an optional embodiment, the preparation method of the silicon-carbon material includes: making the porous carbon in a moving state, heating it to 300°C to 800°C, introducing a silicon-containing gas for reaction, controlling the flow rate of the silicon-containing gas to be 50mL / min to 50L / min, the pressure to be -3kPa to 101kPa, and the introduction time to be 0.5h to 50h, and the mass ratio of the silicon-containing gas to the porous carbon to be 2 to 20:1 during a certain period of the reaction. The present invention ensures that the silicon-based material is deposited in the pores of the porous carbon by comprehensively regulating the deposition temperature, concentration, pressure, flow rate and time, thereby effectively alleviating the expansion and contraction effect of the silicon negative electrode and extending the cycle life of the silicon negative electrode.
[0058] In an optional embodiment, in the method for preparing the silicon-carbon material, the silicon-containing gas includes silane, and the silane is selected from at least one of monosilane, disilane, trisilane, dichlorosilane, trichlorosilane, tetrachlorosilane, and trimethylsilane; in addition, the silicon-containing gas in the present invention may also include chlorosilane, for example, it may be at least one of dichlorosilane, trichlorosilane, and tetrachlorosilane.
[0059] The mass of the silicon-containing gas required for the reaction also depends on the conversion rate of silane (chlorosilane), which can be calculated by the mass of the silicon-based material deposited in the porous carbon / the mass of the silane (chlorosilane), or by analyzing the mass flow rate of the silicon-containing gas at the reactor inlet and the concentration (mol / h) of silane (chlorosilane) and hydrogen in the tail gas to calculate the silane (chlorosilane) conversion rate. In the present invention, the conversion rate of the silicon-containing gas into the silicon-based material is greater than 50%. In a preferred embodiment, the mass ratio of the silicon-containing gas to the porous carbon is 3 to 10:1.
[0060] In an optional embodiment, in the method for preparing the silicon-carbon material, the boiling point of the silicon-containing gas is 20°C to 800°C.
[0061] In an optional embodiment, in the method for preparing the silicon-carbon material, the content of silane in the silicon-containing gas is 1.25 wt.% to 100 wt.%.
[0062] In an optional embodiment, in the method for preparing the silicon-carbon material, the porous carbon is fluidized by a carrier gas and is in convection contact with the silicon-containing gas, and the flow rate of the fluid thus formed is 0.1 m / s to 0.5 m / s, preferably 0.18 m / s to 0.22 m / s.
[0063] In an optional embodiment, in the method for preparing the silicon-carbon material, the flow rate of the carrier gas is 65 mL / min to 50 L / min.
[0064] In an optional embodiment, in the method for preparing the silicon-carbon material, the carrier gas is at least one of hydrogen, argon, and nitrogen.
[0065] In an optional embodiment, in the method for preparing the silicon-carbon material, the volume flow ratio of the carrier gas to the silicon-containing gas is 18 to 24:1, preferably 20 to 23:1.
[0066] In an optional embodiment, in the method for preparing the silicon-carbon material, the heating temperature is 400°C to 700°C.
[0067] In an optional embodiment, in the method for preparing the silicon-carbon material, the introduction time is 1 hour to 20 hours.
[0068] In an optional embodiment, the method for preparing the silicon-carbon material also includes: when the silicon-containing gas is monosilane, the deposition rate of the silicon-based material is determined by monitoring the volume percentage of hydrogen in the reactor exhaust gas (monosilane is cracked to produce silicon-based materials and hydrogen) with reaction time, and the deposition amount of the silicon-based material is determined according to the pore volume of the porous carbon and the need to prepare high silicon content or low silicon content silicon-carbon materials to ensure that silicon is deposited in the pores of the porous carbon, while leaving certain pores to avoid volume expansion. Therefore, the silicon content is generally controlled to be between 10% and 90% of the pore volume of the porous carbon, preferably in the range of 20% to 60%.
[0069] In an optional embodiment, the method for preparing the silicon-carbon material further comprises: passivating the deposited material with a passivating gas, the passivating temperature being 100° C. to 700° C., and the passivating time being 0.1 h to 12 h, preferably 0.1 h to 6 h. The passivating gas is introduced for a sufficient time to allow the passivating gas to undergo a self-terminating hydrosilylation reaction with the surface of the amorphous silicon nanoparticles to obtain passivated silicon-carbon composite particles, so as to prevent the silicon-based material from directly contacting the electrolyte and reduce the irreversible capacity.
[0070] The passivating gas used in the present invention is an organic compound, which can be a non-oxygen-containing passivating gas or an oxygen-containing passivating gas. The non-oxygen-containing gas includes olefins or alkynes, such as acetylene, propylene, ethylene, butene, etc. The oxygen-containing gas includes at least one of ethanol, dimethyl carbonate, ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, vinylene carbonate, allyloxyethanol, diallyl carbonate, allyl methyl carbonate, allyl ethyl carbonate, allyl glycidyl ether, allyloxy (polyethylene oxide) methyl ether and allyloxytrimethylsilane.
[0071] In an optional embodiment, in the method for preparing the silicon-carbon material, the deposited or passivated material is carbon-coated with a carbon source gas, which can improve the conductivity and buffer the expansion at the same time. The reaction temperature of the carbon coating step is 600°C to 1200°C, the reaction time is 3min to 360min, and the carbon source gas is selected from olefins or alkynes, such as acetylene, propylene, ethylene, butene, etc.
[0072] In an optional embodiment, in the method for preparing the silicon-carbon material, the flow rate of the carbon source gas is 0.1 L / min to 15 L / min.
[0073] In an optional embodiment, in the method for preparing the silicon-carbon material, the thickness of the carbon coating layer is 1 nm to 120 nm, preferably 2 nm to 50 nm.
[0074] In an optional embodiment, in the method for preparing the silicon-carbon material, the mass of the carbon coating layer in each silicon-carbon material particle accounts for 1% to 20% of the total mass of the particle.
[0075] In an optional embodiment, the porous carbon is obtained by activating a coke raw material, which may be one or more of petroleum coke, pitch coke, needle coke and coal coke.
[0076] In an optional embodiment, the porous carbon is prepared by pyrolysis and activation in sequence. The polymer material can be an organic polymer, an inorganic polymer, and a synthetic polymer, such as a phenolic compound (phenol, resorcinol, catechol, hydroquinone, phloroglucinol, or a combination thereof) and an aldehyde compound (formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, benzaldehyde, cinnamaldehyde, or a combination thereof) polymerized to form a polymer gel, and then pyrolyzed to obtain it; or bisphenol A and hexamethylenetetramine are polymerized and pyrolyzed to obtain it. The pyrolysis step is to pyrolyze the polymer material at a temperature of 650°C to 1100°C under an inert atmosphere to obtain a pyrolyzed carbon material.
[0077] The present invention activates the porous carbon material obtained by pyrolysis, thereby adjusting the pore structure of the porous carbon. In the activation step, the activation temperature is 650° C. to 1100° C., and the activation gas used is at least one of carbon dioxide and water vapor to obtain an activated porous carbon material.
[0078] In an optional embodiment, the activated porous carbon is heat treated under an inert atmosphere at a temperature of 500°C to 3000°C for a time of 0.5h to 24h to adjust the pore size distribution of the porous carbon so that the porous carbon prepared by the present invention has a porosity of 50% to 90%, wherein micropores account for 10% to 30% and mesopores account for 50% to 85%, thereby making it easier to deposit silicon-based materials.
[0079] In an optional embodiment, a carbon source is used to perform chemical vapor deposition on the activated or heat-treated porous carbon, the reaction pressure is 0.2MPa-0.3MPa, the reaction temperature is 700℃-800℃, and the time is 0.5h-20h. By further depositing carbon on the porous carbon, some pores will be filled or closed, and the pores in the porous carbon with a size of less than 1nm will be closed, thereby increasing the mesoporosity of the porous carbon.
[0080] According to a second aspect of the present invention, there is further provided a negative electrode plate, which comprises a current collector and a membrane arranged on a surface of the current collector, wherein the membrane comprises the silicon-carbon material described in the first aspect.
[0081] According to the third aspect of the present invention, a secondary battery is also provided, comprising a positive electrode sheet, the negative electrode sheet according to the second aspect of the present invention, and an electrolyte located between the positive electrode sheet and the negative electrode sheet. Based on the above characteristics of the silicon-carbon material of the present invention, the secondary battery provided by the present invention also has the advantages of high specific capacity, long cycle life, and good reaction kinetics.
[0082] According to a fourth aspect of the present invention, the present invention further provides an electrical device, comprising the secondary battery described in the third aspect of the present invention.
[0083] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0084] Test method:
[0085] 1. Particle size: Mastersizer 3000 laser diffraction technology is used to measure the particle size. According to the particle size distribution laser diffraction method GB / T19077-2016, the particle size distribution of the modified graphite material sample is measured. Dv50: The particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. Dv50 is also called the median particle size.
[0086] 2. Specific surface area (BET): According to GB / T195872017, the specific surface area analysis method of nitrogen adsorption was used for testing and the specific surface area was calculated by BET (Brunauer Emmett Teller) method.
[0087] 3. Silicon content: Silicon content is defined by the following formula: Silicon content = 100% * (mass of silicon contained in silicon-carbon material) / (mass of silicon-carbon material), in mass%. Fill the sample in the sample cup and measure it by the following method. Use the fundamental parameter method (FP method) to calculate the silicon content (content of Si element) in mass%. Fluorescent X-ray device: NEXCG manufactured by Rigaku; tube voltage: 50 kV; tube current: 1.00 mA; sample cup: Φ32 12mL CH1530; sample weight: 2 to 3 g; sample height: 5 to 18 mm; Fill the sample in the sample cup and measure it by the above method. Use the fundamental parameter (FP method) to calculate the silicon content in the composite particles in mass%.
[0088] 4. Pore volume and porosity: Micromeretics ASAP 2460 is used for micropore and mesopore analysis. At liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its pore size and other characteristics. Combined with the law of the change of adsorption amount with relative pressure during adsorption, multiple models can be fitted to calculate the pore size. The report generated by the software uses the BJHDesorptioncumulative volume of pores model. The pore volume and porosity were calculated within the pore size range.
[0089] 5. Tap density: GB / T5162-2006 is used to measure the tap density of powder on the testing instrument, the Better Tap Density Tester.
[0090] 6. Coating thickness: The material is sectioned using a FIB-SEM device, and the average coating thickness is measured in the SEM.
[0091] 7.I D / I G Test: Raman spectroscopy test shows that the composite negative electrode material has a -1 ~1400cm -1 Peak intensity in the range I D With 1580cm -1 ~1620cm -1 Peak intensity in the range I G The ratio I D / I G .
[0092] 8. True density: The true density of the material is tested in accordance with GB / T 24533-2019, and the test equipment uses a true density tester (BEST, 3H-2000TD).
[0093] 9. Compaction density: The compaction density of the material is tested in accordance with GB / T 24533-2019, and the test equipment uses a compaction density meter (McNor, CARVER 4350).
[0094] Example 1
[0095] This embodiment provides a method for preparing a silicon-carbon material, comprising the following steps:
[0096] (1) Preparation of porous carbon
[0097] Petroleum coke was used as a carbon precursor. Petroleum coke and KOH (solid activator) were uniformly mixed at a mass ratio of 1:2. After mixing, the mixture was placed in a rotary kiln and heated to 800°C at a heating rate of 4°C / min. N 2As a protective gas, water vapor was introduced after the temperature rose to 850°C, with a flow rate of 0.16 mL / g / s, and the temperature was kept for 3 hours, and then the steam was turned off to obtain a porous carbon material. The porous carbon was crushed to Dv50 2 The specific surface area of porous carbon is 7.4 μm; the specific surface area of porous carbon is 2000 m 2 / g; pore volume is 0.96cm 3 / g.
[0098] (2) Deposition of silicon-based materials
[0099] 1 kg of porous carbon was weighed into the reactor, purged to remove oxygen, and the leak point was detected before heating. 4 ) is the silicon source, nitrogen is used as the carrier gas, the silicon source flow rate is 3L / min, and the carrier gas flow rate is 12L / min. In a chemical vapor deposition furnace, the reaction temperature is 500°C for 6 hours, and the nano-silicon is deposited into the porous carbon pores. The fluidized bed pressure is controlled to -2kPa; then, the temperature is controlled to maintain 580°C, 3L / min of acetylene gas is introduced, the acetylene time is 60min, and the fluidized bed pressure is controlled to 6kPa. Stop the introduction of acetylene gas, and keep the inert gas introduction until the reaction product cools to room temperature to obtain silicon-carbon particles and obtain negative electrode active materials. The chemical vapor deposition furnace is a vertical fluidized bed equipment.
[0100] The silicon-carbon material prepared in this embodiment includes an active substance and a coating layer located on at least part of the surface of the active substance, wherein the active substance includes a porous carbon matrix and amorphous silicon filled in the pores of the porous carbon matrix. The coating layer is a carbon layer. The silicon content in the silicon-carbon material is 51wt.%; the Dv50 of the silicon-carbon material is 1 The specific surface area of silicon carbon material is 7.8μm; the specific surface area of silicon carbon material is 1.5m 2 / g;BET 1 ×(Dv50 2 / Dv50 1 )=1.42.
[0101] Example 2
[0102] The difference between this embodiment and embodiment 1 is that the silicon source flow rate is 2 L / min, the carrier gas flow rate is 30 L / min, and the reaction time of chemical vapor deposition is 12 h. The silicon content in the silicon-carbon material is 70 wt.%; the Dv50 of the silicon-carbon material 1 The specific surface area of silicon carbon material is 8.1μm; the specific surface area of silicon carbon material is 0.9m 2 / g;BET 1 ×(Dv50 2 / Dv50 1 )=0.82.
[0103] Example 3
[0104] The difference between this embodiment and embodiment 1 is that the silicon source flow rate is 10 L / min, the chemical vapor deposition temperature is 520°C, and the chemical vapor deposition reaction time is 4 hours. The silicon content in the silicon-carbon material is 20 wt.%; the Dv50 of the silicon-carbon material is 1 The specific surface area of silicon carbon material is 7.5μm; the specific surface area of silicon carbon material is 6.5m 2 / g;BET 1 ×(Dv50 2 / Dv50 1 )=6.41.
[0105] Example 4
[0106] The difference between this embodiment and embodiment 1 is that the pressure of the fluidized bed is controlled to be -1 kPa. The silicon content in the silicon-carbon material is 60 wt.%; the Dv50 of the silicon-carbon material is 1 The specific surface area of silicon carbon material is 7.8μm; the specific surface area of silicon carbon material is 1.2m 2 / g;BET 1 ×(Dv50 2 / Dv50 1 )=1.14.
[0107] Example 5
[0108] The difference between this embodiment and embodiment 1 is that the silicon source flow rate is 5 L / min, and the reaction time of chemical vapor deposition is 4 h. The silicon content in the silicon-carbon material is 45 wt.%; the Dv50 of the silicon-carbon material is 1 The specific surface area of silicon carbon material is 7.6μm; the specific surface area of silicon carbon material is 3.1m 2 / g;BET 1 ×(Dv50 2 / Dv50 1 )=3.02.
[0109] Example 6
[0110] The difference between this embodiment and embodiment 1 is that the porous carbon particles are crushed to a size of Dv50 2 The silicon content in the silicon-carbon material is 53wt.%; the Dv50 of the silicon-carbon material 1 The specific surface area of silicon carbon material is 1.4m 2 / g;BET 1 ×(Dv50 2 / Dv50 1 )=1.31.
[0111] Example 7
[0112] The difference between this embodiment and embodiment 1 is that the porous carbon particles are crushed to a size of Dv502 The silicon content in the silicon-carbon material is 48wt.%; the Dv50 of the silicon-carbon material 1 The specific surface area of silicon carbon material is 1.6m 2 / g;BET 1 ×(Dv50 2 / Dv50 1 )=1.52.
[0113] Comparative Example 1
[0114] The only difference between this comparative example and Example 1 is that the carrier gas flow rate is 200 L / min. The silicon content in the silicon-carbon material is 5 wt.%; the Dv50 of the silicon-carbon material is 1 The specific surface area of silicon carbon material is 7.4μm; the specific surface area of silicon carbon material is 1750m 2 / g;BET 1 ×(Dv50 2 / Dv50 1 )=1750.
[0115] Comparative Example 2
[0116] The only difference between this comparative example and Example 1 is that the silicon source flow rate is 1 L / min, the carrier gas flow rate is 30 L / min, and the reaction time of chemical vapor deposition is 16 h. The silicon content in the silicon-carbon material is 75 wt.%; the Dv50 of the silicon-carbon material 1 The specific surface area of silicon carbon material is 0.5m 2 / g;BET 1 ×(Dv50 2 / Dv50 1 )=0.46.
[0117] Electrochemical performance test
[0118] Preparation of button half-cell: The negative electrode active materials, conductive additive carbon black, and adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) obtained in each embodiment and comparative example are weighed according to a mass ratio of 94:2:4, and slurry is prepared with a beater to obtain negative electrode slurry; then the above-mentioned negative electrode slurries are coated on the surface of the negative electrode current collector (specifically copper foil), and then dried and cut into pieces in turn, and assembled into button batteries with lithium metal sheets in a glove box. At a constant temperature of 25±2℃, a constant current charge and discharge mode test is performed using a charge and discharge instrument, the discharge cut-off voltage is 0.005V, and the charge cut-off voltage is 2V. The first week of charge and discharge test is performed at a current density of 1C / 10 to obtain the reversible specific capacity and the first coulomb efficiency. First coulomb efficiency = first charge capacity / first discharge capacity×100%.
[0119] Preparation of a full battery: The negative electrode active materials prepared in each embodiment and comparative example are configured with graphite to form a composite with a specific capacity of 450 mAg / h, and then mixed with a conductive additive and a binder at a mass ratio of 94:2:4 to prepare a negative electrode slurry, and the negative electrode slurry is coated on a current collector (specifically copper foil) to obtain a negative electrode sheet; the positive electrode active material LiCoO 2 , conductive carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a weight ratio of 96.7:1.7:1.6, and then coated on Al foil, dried, and cold pressed to obtain a positive electrode sheet; a polypropylene porous polymer film is used as an isolation membrane; the above-mentioned positive electrode sheet, isolation membrane, and negative electrode sheet are stacked in order, so that the isolation membrane is between the positive electrode sheet and the negative electrode sheet to play an isolation role, and then wound to obtain a bare battery cell. The bare battery cell is placed in an outer package, injected with the prepared electrolyte and packaged, and a full battery cell is obtained through a process of formation, degassing, trimming, etc. The electrolyte is a common formula of silicon-adapted negative electrode electrolyte on the market.
[0120] Battery expansion rate test: At 25°C, the above full batteries were subjected to constant current charge and discharge tests using a charge and discharge instrument, with a discharge cut-off voltage of 2.75V and a charge cut-off voltage of 4.2V. The charge and discharge tests were all conducted at a current density of 1C. After 100 cycles, the expansion rate of each battery was determined using an in-situ expansion analysis system, and the results are summarized in Table 1. The capacity retention rate after 300 cycles was also recorded, and the capacity retention rate = discharge capacity at the 300th cycle / discharge capacity at the 1st cycle × 100%.
[0121] Table 1 Electrochemical data
[0122]
[0123]
[0124] It can be seen from the data in Table 1 that the silicon-carbon material provided by the embodiment of the present invention has a silicon content of 20 wt.% to 70 wt.%, and a specific surface area BET 1 (m 2 / g) and median particle size Dv50 1 (μm) and the median particle size Dv50 of porous carbon 2 (μm) satisfies 0.8≤BET 1 ×(Dv50 2 / Dv50 1 )≤6.5, it can effectively alleviate the expansion and contraction effect of the silicon negative electrode and also have a higher reversible specific capacity, so that the silicon-carbon material provided by the present invention can be used as the negative electrode active material of the secondary battery.
[0125] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A silicon-carbon material, characterized in that: The silicon-carbon material comprises porous carbon and a silicon-based material located in the pores of the porous carbon; the silicon content in the silicon-carbon material is 20wt.% to 70wt.%, and the specific surface area BET1 of the silicon-carbon material and the median particle size Dv501 of the silicon-carbon material and the median particle size Dv502 of the porous carbon satisfy the following conditions: 0.8≤BET1×(Dv502 / Dv501)≤6.5; The unit of BET1 is m 2 / g, the unit of Dv501 and Dv502 is μm.
2. The silicon-carbon material according to claim 1, characterized in that: The silicon content in the silicon-carbon material is 48 wt.% to 55 wt.%, and 1.0≤BET1×(Dv502 / Dv501)≤3.
0.
3. The silicon-carbon material according to claim 1 or 2, characterized in that: 0.3m 2 / g≤BET1≤5m 2 / g; preferably, 0.5m 2 / g≤BET1≤2m 2 / g; And / or, 1 μm≤Dv501≤20 μm; preferably, 2 μm≤Dv501≤10 μm.
4. The silicon-carbon material according to claim 1 or 2, characterized in that: The silicon-based material includes one or more of amorphous silicon, crystalline silicon, and a composite of crystalline silicon and amorphous silicon.
5. The silicon-carbon material according to claim 1 or 2, characterized in that: The pore volume of the silicon-carbon material is less than 0.5 cm 3 / g, preferably less than 0.1cm 3 / g; And / or, the true density of the silicon-carbon material is 1.5 g / cm 3 ~3g / cm 3 ; And / or, the tap density of the silicon-carbon material is td Meet: 0.5g / cm 3 ≤ρ td ≤1.2g / cm 3 ; And / or, the compaction density of the silicon-carbon material under a pressure of 5T is cd Meet: 0.5g / cm 3 ≤ρ cd ≤2g / cm 3 ; And / or, the Raman spectrum of the silicon-carbon material is D / I G Less than 2.
6. The silicon-carbon material according to claim 1 or 2, characterized in that: The silicon-based material fills 10% to 90% of the pore volume of the porous carbon, preferably 20% to 60%; And / or, the specific surface area BET2 of the porous carbon satisfies: 200m 2 / g≤BET2≤4000m 2 / g; preferably, 500m 2 / g≤BET2≤2000m 2 / g; And / or, the pore volume of the porous carbon is 0.4 cm 3 / g~2.5cm 3 / g; and / or, the porosity of the porous carbon is 50% to 90%; And / or, the true density of the porous carbon is 1 g / cm 3 ~3g / cm 3 .
7. The silicon-carbon material according to claim 1 or 2, characterized in that: The silicon-carbon material further includes a coating layer, and the coating layer includes one or more of a carbon coating layer, an oxide coating layer, a metal salt coating layer, and a polymer coating layer; And / or, the coating layer has a thickness of 5 nm to 500 nm; And / or, the mass of the coating layer accounts for 1% to 20% of the total mass of the silicon-carbon material.
8. A negative electrode plate, characterized in that: The negative electrode plate includes a current collector and a membrane disposed on a surface of the current collector, and the membrane includes the silicon-carbon material according to any one of claims 1 to 7.
9. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet as claimed in claim 8, and an electrolyte located between the positive electrode sheet and the negative electrode sheet.
10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.
Citation Information
Patent Citations
Silicon-carbon negative electrode material and preparation method thereof
CN116826017A
Silicon carbon material and preparation method thereof, negative electrode material, negative electrode plate, battery and electric device
CN117334869A
Silicon-carbon composite material, negative pole piece, electrochemical device and electronic device
CN118136791A
Silicon-carbon composite material, negative plate and battery
CN118213508A
Negative active material and preparation method thereof, negative pole piece and secondary battery
CN118472243A
Cited By
Carbon source mixed gas CVD coated silicon carbon negative electrode material, preparation method and lithium ion battery
CN120261549A